FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Hengky, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is examine the analysis of factors affecting financial performance of companies listed on Indonesian Stock Exchange for the period 2016-2018. Sample was selected using purposive sampling method amounted to 33 companies. Data processing techniques using multiple regression analysis what helped by Eviews program10.0 (Economic Views) for windows released 20 and Microsoft Excel 2007. The result shown in this research indicates that environmental acocunting, sustainability reporting and managerial ownership as one of the corporate governance proxies used in this research does not have any postive significance effect on financial performance, whereas, institusional ownership as the other proxy shows a positive significance effect.